Influence of Guided Inquiry Model on Students Cognitive Learning Outcome in Stoichiometrytopic (Journal of Innovative Science Education, 2018)
Teacher as a facilitator is expected to explore the potential of students to be able to master the material with minimal mastery. This research aims to understand the concept of students' increased understanding of the material stoichiometry with guided inquiry learning model application. Experimental research conducted in SMAN 6 Semarang. The research sample is determined by purposive sampling class X MIPA 7 (an experimental class with 36 students) and Class X MIPA 8 (a control class with 36 students). Theused instrument is a cognitive achievement test. Analysis of students' cognitive learning outcomes data using the N-gain average test obtained 80.94%, with the average of an experimental group of students by 83.00% and theaverage of control group students by 76.94%. Achievement of experimental class minimum completeness criteria 91.67% and a standard deviation of 6.21 is higher than the minimum completeness criteria for achievement grade control by 69.44% and a standard deviation of 7.38. The t-test analysis obtained t value of 57.61 is greater than t table at a significance level of 0.05 by 2.03. The results of the analysis stated that there is significant influence guided inquiry learning model application of the cognitive achievement of students on the concept of stoichiometry.